Expert System for Mental Health Disordes in Women and Children based on Android using the Certainty Factor Method - Lasena, Marlin; Gobel, Citra Yustitya; Puspa, Misrawati Aprilyana (SISTEMASI, 2026)
This study focuses on the limited access to mental health services in Gorontalo and the social stigma surrounding mental health disorders, which discourages women and children from seeking help. The main problem addressed in this research is the management of mental health disorders, particularly the complexity of the initial diagnostic process. The study aims to develop an expert system using the Certainty Factor method to assist in the early diagnosis of mental health disorders in women and children, specifically Depression, Anxiety, and Stress disorders. The research employs a Research and Development (R&D) approach with qualitative methods, including interviews with experts such as psychologists to obtain a knowledge base comprising symptoms, Measure of Belief, and Measure of Disbelief values. The expert system is implemented on the Android platform, facilitating user access to early diagnostic services. Results from the Certainty Factor calculations on user data indicate that the early diagnosis confidence levels are 97.04% for Depression, 63.11% for Anxiety, and 59.72% for Stress. The highest value is observed for Depression, suggesting that the symptoms selected by users most strongly indicate this disorder, with the highest confidence level across all Depression symptoms. Both manual calculations by experts within the system and Black Box testing confirm that the Certainty Factor method can effectively support early diagnosis of mental health disorders. The study concludes that the expert system using the Certainty Factor method is effective and can be implemented as an early mental health detection tool. The strength of this research lies in the integration of qualitative expert knowledge with mobile technology implementation, providing a practical and easily accessible solution for the community.